Epidemiology of Q-fever in domestic ruminants and humans in Africa: A systematic review - Bwatota, S.F.; Cook, Elizabeth A.J.; Bronsvoort, B.M. de C.; Wheelhouse, N.; Hernandez-Castro, L.E.; Shirima, G.M. (CAB International, 2022)
Q-fever is a zoonotic infectious disease caused by the gram-negative, intracellular, spore-forming bacterium Coxiella burnetii. Infected ruminants (cattle, sheep, and goats) are the reservoirs of the pathogen and thus an important source of infection in humans. This systematic review aims to consolidate the knowledge and awareness of Q-fever in Africa and identify future research opportunities and possible interventions in low-resource settings. We review information on Q-fever epidemiology and the diagnostic challenges in humans and domestic ruminants in Africa from the last 23 years. Six databases including university repositories were searched for relevant articles. A total of 84 studies and 4 theses met the selection criteria and were thus included in the review. They include serological and molecular studies of Q-fever in humans or domestic ruminants in 24/54 African countries. The mean seroprevalence estimates were 16% (95%CI 11–23%) in humans; 14% (95%CI 10–20%) in cattle; 13% (95%CI 9–18%) in sheep; and 21% (95%CI 15–29%) in goats. The mean prevalence for molecular detection of the pathogen were 3% (95%CI 0–16%) in humans; 9% (95%CI 4–19%) in cattle; 16% (95%CI 5–41%) in sheep; and 23% (95%CI 20–80%) in goats. The number of studies that identified risk factors for exposure among domestic ruminants was: sex (n = 6), age (n = 17), contact with other animals (n = 5), lack of quarantine of newly purchased animals (n = 1), extensive grazing system (n = 4), herd size (2), history of abortion (n = 5), absence of vaccination (n = 2), and high temperature (n = 1). The number of studies that reported protective factors was: sanitation (n = 2), burying and/ or burning the aborted foetus (n = 2), and young (age) (n = 2). The studies that identified risk factors for human disease infection included: close contact to animals (n = 7), age (n = 3), and gender (n = 5), while those identifying protective factors included: living in non-irrigated areas (n = 1), awareness/knowledge about zoonosis (n = 1), rodent control (n = 1), sanitation/disinfection of equipment after and before use (n = 1), occasional grazing (n = 1), and do nothing to aborted materials (n = 1). Diagnostic challenges such as poverty, lack of a well-equipped laboratory with biosafety level 3 specific for Q-fever testing, unspecific and self-limiting clinical signs/symptoms, lack of gold standard test, and variation in test specificity and sensitivity were identified. The disease is likely to be widespread in Africa and of public importance and underreported thus ‘One Health’ approaches to future studies are recommended. Further studies should focus on concurrent studies of human and livestock populations.